Dynamics of Zonation System Implementation at Senior High School 9 Gowa - Syarifuddin Syarifuddin; Shermina Oruh; Andi Agustang (Universitas of Muhammadiyah Makassar, 2022)
This study examined the Dynamics of Zoning System Implementation in the acceptance of new students at SMA Negeri 9 Gowa. This study aimed to describe the dynamics of the implementation of the zoning system and the implications of the implementation of the zoning system in SMA Negeri 9 Gowa district. The research method of this research was qualitative with a phenomenological approach, data collection techniques through primary data and primary data, primary data by means of observation and interviews and secondary data by collecting from literature studies. This study used the theory of psychology and structuralism, typology of social change and structural functionalism as analytical tools in revealing research problems accurately. The results of the study showed (i) the dynamics of implementing the student admission process using the zoning system in addition to the long process, all registration transactions were carried out online, besides that there were still some prospective registrants who were constrained by the technological facilities that would be used to register (did not have a mobile phone or computer to access In addition, the accuracy of the location zone data for prospective students which is not yet accurate makes parents of prospective students confused and feel there was no certainty that their children would be enrolled in the destination school or in another school. (ii) the implication of the application of the zoning system for new student admissions was that all school statuses were equalized and there were no more excellent school titles, but on the other hand, the existence of a zoning system creates the behavior of unscrupulous parents who manipulate population data (capil) by entrusting their children on the card. relatives who were around the destination school, especially in SMA Negeri 9 Gowa district.Penelitian ini mengkaji tentang Dinamika Implementasi Sistem Zonasi dalam penerimaan peserta didik baru di SMA Negeri 9 Gowa. Penelitian ini bertujuan untuk mendeskripsikan bentuk dinamika implementasi sistem zonasi dan implikasi penerapan sistem zonasi di SMA Negeri 9 kabupaten Gowa. Metode penelitian penelitian ini adalah kualitatif dengan pendekatan fenomenologi, teknik pengumpulan data melalui data primer dan data sekunder, data primer dengan cara observasi dan wawancara kemudian data sekunder dengan pengumpulan dari studi pustaka. Penelitian ini menggunakan teori psikologi dan strukturalisme, tipologi perubahan sosial dan fungsionalisme struktural sebagai pisau analisis dalam mengungkap masalah penelitian secara akurat. Teknik penentuan informan penelitian dengan menggunakan proposive sampling, teknik pengumpulan data melalui observasi, dokumentasi dan wawancara. Teknik analisis melaluireduksi data, penyajian data, dan penarikan kesimpulan.Adapunhasil penelitian menunjukkan (i) dinamika implementasi proses penerimaan peserta didik dengan menggunakan sistem zonasi selain prosesnya yang panjang semua transaksi pendaftaran dilakukan secara daring, selain itu masih ada beberapa calon pendaftar terkendala pada fasilitas teknologi yang akan digunakan mendaftar (belum memiliki handphone atau komputer untuk mengakses internet) disamping itu akurasi data zona lokasi calon peserta didik yang belum akurat menjadikan para orang tua calon peserta didik kebingungan dan mersa tidak ada kepastian anaknya akan terdaftar di sekolah tujuan atau justru di sekolah lain. (ii) implikasi penerapan sistem zonasi penerimaan peserta didik baru menjadikan semua status sekolah disederajatkan dan tidak ada lagi gelar sekolah unggulan, akan tetapi disisi lain dengan adanya sistem zonasi menjadikan adanya perilaku oknum orang tua yang memanipulasi data kependudukan (capil) dengan menitip anaknya di kartu keluarga kerabat yang ada di sekitar sekolah tujuan terutama di SMA Negeri 9 kabupaten Gowa.